2019
DOI: 10.3892/ol.2019.10653
|View full text |Cite
|
Sign up to set email alerts
|

Notch and breast cancer metastasis: Current knowledge, new sights and targeted therapy (Review)

Abstract: Breast cancer is the most common type of invasive cancer in females and metastasis is one of the major causes of breast cancer-associated mortality. Following detachment from the primary site, disseminated tumor cells (DTCs) enter the bloodstream and establish secondary colonies during the metastatic process. An increasing amount of studies have elucidated the importance of Notch signaling in breast cancer metastasis; therefore, the present review focuses on the mechanisms by which Notch contributes to the occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 168 publications
0
26
0
Order By: Relevance
“…Pin1 also promotes EMT through upregulation of STAT3 and NF-κB in human gallbladder cancer [ 172 ]. Additionally, NOTCH signaling drives metastasis in numerous cancers [ 173 , 174 , 175 , 176 ] and Pin1 prevents NOTCH1 and NOTCH4 from undergoing FBXW7-mediated degradation, leading to an increase in breast cancer stem cells’ (CSCs) self-renewal and metastasis [ 177 ]. In addition to protein stability, Pin1 also activates NOTCH1 transcriptional activity by facilitating γ-secretase-mediated cleavage and release of the active intracellular domain.…”
Section: Dysregulation Of Pin1 Signaling In Tumorigenesismentioning
confidence: 99%
“…Pin1 also promotes EMT through upregulation of STAT3 and NF-κB in human gallbladder cancer [ 172 ]. Additionally, NOTCH signaling drives metastasis in numerous cancers [ 173 , 174 , 175 , 176 ] and Pin1 prevents NOTCH1 and NOTCH4 from undergoing FBXW7-mediated degradation, leading to an increase in breast cancer stem cells’ (CSCs) self-renewal and metastasis [ 177 ]. In addition to protein stability, Pin1 also activates NOTCH1 transcriptional activity by facilitating γ-secretase-mediated cleavage and release of the active intracellular domain.…”
Section: Dysregulation Of Pin1 Signaling In Tumorigenesismentioning
confidence: 99%
“…The American Cancer Association states that BC can be classified into four BC molecular subtypes with prognostic differences in terms of patient outcome on the basis of the presence or absence of the expression of specific biological markers: ERs, progesterone receptors, and HER2. The Notch system, in cooperation with the VEGF pathway, engages in the adjusting of angiogenesis and sprouting in BC (Zhang et al, 2019). Notch expression is controlled by hypoxia and inflammatory cytokines (IL-1, IL-6, and leptin).…”
Section: Notch Pathway and Bcmentioning
confidence: 99%
“…As a potential factor in cell fate, increasing evidence has shown that Notch signaling plays like a double-edged sword in cancer, and it has both oncogene and onco-suppressor activities [ 248 , 249 , 250 , 251 , 252 , 253 , 254 ]. It has been reported that metastasis of GC cells is tightly regulated by Notch/PTEN/Akt axis.…”
Section: Upstream Modulators Of Ptenmentioning
confidence: 99%